Analisis Hubungan Manajemen Laba dan Struktur Kepemilikan Terhadap Kinerja Perusahaan di BEI Tahun 2016-2019 - Sari Dewi; Lisa Lisa (Owner : Riset dan Jurnal Akuntansi, 2021)
Firm performance includes the activities produced by company management and high firm performance can be said to allow them to plan their work according to their own goals and take risks with full responsibility. This study was conducted to determine the effect of earnings management, the size of the board of directors, and ownership structure (blockholders ownership, institutional ownership, family ownership, and managerial ownership) on the firm's performance. By using sample data listed on the Indonesia Stock Exchange (IDX) from 2016 to 2019. Because there are several previous studies that produce different values ?? on firm performance. Therefore, it is necessary to re-examine this. In this study using the firm's performance with Tobin's Q model to determine the value of asset management generated by the company. The data used is panel data with secondary data collection techniques to test outliers by SPSS software version 25, then test descriptive statistics, multicollinearity, heteroscedasticity, R Square, F test, and also t-test using Eviews software version 10. The results of this study conclude that both accrual-based and real earnings management have a significant positive effect on firm performance, while the size of the board of directors has a significant negative effect on performance. The ownership structure has no significant effect on the firm's performance. The result of insignificant results could be caused by not supporting the agency theory perspective, as well as the lack of company control.